Building capacity for civic learning and engagement: An emerging infrastructure in the academic arts and humanities in the United States. (July 2015) - Heiland, Donna; Huber, Mary Taylor
American higher education has always articulated a civic mission as part of its purpose: colleges and universities educate students for life in a democratic society and provide that society with citizens who ensure that it thrives in turn. This essay maps the development of a national infrastructure for civic learning and engagement in American higher education, with a focus on the mid-1980s onward, when—after a period of relative eclipse—this work gained new coherence and momentum. Beginning with that moment of eclipse, when an intensified and professionalized research mission threatened to overshadow higher education's civic commitments, we adumbrate briefly the countermovements that allowed the civic mission of colleges and universities to reassert itself. We then discuss the civic engagement networks that have emerged over the past three decades, and more recent partnerships and projects that have expanded understanding of higher education's civic commitment in the 21st century.